Pangenome reconstruction in rats enhances genotype-phenotype mapping and variant discovery - Villani, Flavia; Guarracino, Andrea; Ward, Rachel R; Green, Tomomi; Emms, Madeleine; Pravenec, Michal; Sharp, Burt; Prins, Pjotr; Garrison, Erik; Williams, Robert W; Chen, Hao; Colonna, Vincenza (iScience, 2025)
The HXB/BXH family of recombinant inbred rat strains is a unique genetic resource that has been extensively phenotyped over 25 years, resulting in a vast dataset of quantitative molecular and physiological phenotypes. We built a pangenome graph from 10x Genomics Linked-Read data for 31 recombinant inbred rats to study genetic variation and association mapping. The pangenome includes 0.2Gb of sequence that is not present the reference mRatBN7.2, confirming the capture of substantial additional variation. We validated variants in challenging regions, including complex structural variants resolving into multiple haplotypes. Phenome-wide association analysis of validated SNPs uncovered variants associated with glucose/insulin levels and hippocampal gene expression. We propose an interaction between Pirl1l1, chromogranin expression, TNF-α levels, and insulin regulation. This study demonstrates the utility of linked-read pangenomes for comprehensive variant detection and mapping phenotypic diversity in a widely used rat genetic reference panel.